Investigation Science Process Skills Among Chemistry Education Students Through the Law of Mass Conservation Experiment - Aini, Nur (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Abstrack Scientific process skills (SPS) are essential competencies that students must develop through practicum activities. The purpose of this study was to identify students' SPS in the aspects of observing, classifying, interpreting, using tools and materials, and communicating in practicum on the law of conservation of mass. This study used a quantitative descriptive approach method. The research subjects consisted of 30 first semester students of the chemistry education study program at FKIP Tanjungpura University who took basic chemistry practicum courses. The instrument used was an observation sheet. The science process skills (SPS) observation sheet has been validated by two experts which shows a validity value of 0.91 including in the very high category. The results showed that the average percentage obtained for each indicator of students' SPS in the aspects of observing reached 87% (very good), classifying 83% (very good), interpreting 69% (good), using tools/materials 83% (very good), and communicating aspel 79% (good). Overall, the average percentage of students' SPS was 80% with a good category